EWaS3 2018 2018
DOI: 10.3390/proceedings2110606
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Water to Aid Food Security—Perceptions/Acceptance of Consumers toward Urine Based Fertilizer

Abstract: Yellow water is a segregated domestic wastewater stream resulting from Ecological Sanitation (ECOSAN). It is mainly source separated human urine which is rich in nutrients. The potential contribution of yellow water as fertilizer to food security is considerable. The use of this potential however is related to the acceptance of the consumers towards urine based fertilizers (UBF). This work aims to assess acceptance of consumers towards UBF and urine diverting toilets (UDT) for separation of urine, through ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
2
Order By: Relevance
“…When analyzed more closely, the data showed that two predictors most influenced respondent attitudes towards the use of NUF as a fertilizer: age and ward type. The logistic regression model shows that younger respondents (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and citizens living in the rural areas of the municipality displayed the largest magnitude of attitude change between the use of raw and treated urine for fertilizer use. Based on these results, we infer that the younger age cohorts are more open and trusting of the nitrification process employed to treat the urine than older respondents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When analyzed more closely, the data showed that two predictors most influenced respondent attitudes towards the use of NUF as a fertilizer: age and ward type. The logistic regression model shows that younger respondents (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and citizens living in the rural areas of the municipality displayed the largest magnitude of attitude change between the use of raw and treated urine for fertilizer use. Based on these results, we infer that the younger age cohorts are more open and trusting of the nitrification process employed to treat the urine than older respondents.…”
Section: Discussionmentioning
confidence: 99%
“…As our results show, this will depend in large part on the logic that formed public attitudes towards nutrient recycling. In regions where attitudes towards nutrient recycling are shaped primarily by public health concerns [27,28], it is likely that sanitation technology can accrue higher levels of legitimacy than in regions with attitudes shaped by other factors. Although regulatory bodies in countries such as Switzerland [29] have recently amended existing laws to allow the use of NUF as a fertilizer for food crops, the use of human waste as a fertilizer is currently banned in South Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as seen in reading and writing exercises. This kind of perception usually makes them feel quite satisfied if their children have been able to demonstrate certain physical skills even without knowledge of the meaning and nature and purpose of these skills (Taher, Basar, Abdelrahman, & Beler-Baykal, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Apesar de uma aceitação moderada, as pessoas acreditam que a urina humana tem risco à saúde e pode ser nociva às plantas, segundo Lienert et al (2003); Matsebe e Moilwa (2007); Duncker e Matsebe (2008); Mariwah e Drangert (2011); Okem et al (2013); Nimoh et al (2014aNimoh et al ( , 2014b; Mugivhisa e Olowoyo (2015); Simha et al (2018). Para os agricultores, pouco mais da metade pensa que esta é uma opção viável, (LIENERT et al, 2003;LONG, 2011;MÜLLER;PEDRO;FREITAS, 2017;SIMHA et al, 2018;TAHER et al, 2018), porém, o nível da aceitação do consumo de produtos das plantas fertilizadas com urina humana é, na maioria das vezes, inferior ao da aceitação de plantas fertilizadas por produtos convencionais (MAGIVHISA; OLOWOYO, 2015;IGNACIO et al, 2018;SIMHA et al, 2018 No Brasil, ainda são muito poucas as iniciativas para implantação de saneamento ecológico, bem como pesquisas de aceitação do uso de excretas como fertilizantes. Para um melhor entendimento das diferentes barreiras desta prática, é necessário conhecer melhor as percepções dos agricultores familiares, tanto em relação à aceitação da utilização de urina humana como fertilizante, quanto ao consumo das plantas fertilizadas dessa forma.…”
unclassified